Understanding Parkinson's through visual narratives: "I'm not Mrs. Parkinson's". (February 2018) - Lutz, Sara G; Holmes, Jeffrey D; Rudman, Debbie Laliberte; Johnson, Andrew M; LaDonna, Kori A; Jenkins, Mary E
Introduction: Although it is accepted that individuals with Parkinson's disease must navigate challenges such as receiving their diagnosis and changing daily occupations, little is known about how they navigate. The purpose of this study is to deepen the current understanding of the experience of living with Parkinson's disease and its implications for occupation through a narrative visual methodology (photo-elicitation). Method: Six individuals with Parkinson's disease were asked to take photographs and share verbal narrative accounts to illustrate their experience of living with Parkinson's disease. Findings: Results highlight the interrelationship between occupation and identity, as many of the participants' stories were interpreted as foregrounding the negotiation of occupation, and how such negotiation shaped their sense of identity. Overall, three major themes were identified: (1) Framing the meaning of Parkinson's disease (accepting the disease as part of who they were); (2) Negotiating engagement in occupation (ongoing deliberation over whether to continue engaging in certain aspects of life as Parkinson's disease progressed); and (3) Being ready to accept changes that impact personal or social identity (readiness to accept help and to identify as someone with Parkinson's disease). Conclusion: Attending to insights regarding the lived experience of Parkinson's disease will enhance quality of care through informing an enriched client-centered, occupation-based approach.